Marked global differences in mortality in male patients with COVID-19: an analysis of the CARDIO COVID 19-20 and WHF COVID-19 CVD studies - Gómez-Mesa, Juan Esteban; Arango-Ibanez, Juan Pablo; Perel, Pablo; Prabhakaran, Dorairaj; León-Giraldo, Hoover O.; Toro-Pedroza, Alejandro; Gómez, Ricardo Enrique Larrea; Herrera, César J.; Lugo-Peña, Julián; Alaz, Liliana Patricia Cárdenas; Rossel, Victor; Sierra-Lara, Daniel; et al. (Global heart, 2025)
Background: COVID-19 has led to nearly seven million deaths and male sex has been reported as one of the main risk factors for mortality. Few studies have analyzed cohorts of male patients, especially in underrepresented regions in the medical literature, such as low and middle-income nations. To address this gap, we conducted large-scale, male-specific, multinational analyses, to improve understanding of factors associated with mortality in this high-risk population and global variations. Methods: This is a prospective, multicenter study that includes data from the CARDIO COVID-19–20 registry and the WHF COVID-19 CVD study. A multiple Poisson regression model was performed to evaluate differences in factors associated with in-hospital mortality among male COVID-19 patients across different regions. Results: We analyzed 4,899 hospitalized male COVID-19 patients from 32 countries: Africa (11.2%), the Americas (44.7%), Asia (33.8%), and Europe (10.2%). Median age was 59 years (IQR: 47–69), with 50.5% aged 40–64. ICU admission was 42.4%, and mortality was 19.2%, with marked regional differences (ranging from 6% in Europe to 26.9% in the Americas). Poisson regression showed age >80 years (aRR = 4.21) and IMV (aRR = 3.80) as the strongest factors associated with mortality. Other factors included diabetes, chronic kidney disease, myocarditis, and decompensated heart failure. Mortality risk was higher in Africa (aRR = 3.86), Asia (aRR = 2.72), and the Americas (aRR = 2.23) compared to Europe (p < 0.001). Anticoagulation/Antiplatelet therapy showed a potential correlation with survival. Conclusion: This study reflects the complexity of factors influencing COVID-19 mortality among male patients hospitalized with COVID-19, emphasizing global variability. The substantial differences in mortality noted across countries are likely due to differences in disease severity, comorbidities, clinical care, and health system factors. Age remains a primary risk factor, with older populations particularly vulnerable. Our findings underscore the need for targeted and tailored regional approaches to manage male COVID-19 patients.